2014
DOI: 10.1002/tox.22081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofin vitrotoxicity of silver ions and silver nanoparticles on human hepatoma cells

Abstract: Scientific information on the potential harmful effects of silver nanoparticles (AgNPs) on human health severely lags behind their exponentially growing applications in consumer products. In assessing the toxic risk of AgNP usage, liver, as a detoxifying organ, is particularly important. The aim of this study was to explore the toxicity mechanisms of nano and ionic forms of silver on human hepatoblastoma (HepG2) cells. The results showed that silver ions and citrate-coated AgNPs reduced cell viability in a dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 50 publications
8
58
1
1
Order By: Relevance
“…Several reports show that AgNPs enter HepG2 cells localizing in the cytoplasm [34][35][36][37][38][39][40], nuclei [41] and mitochondria [35] at large amount irrespective of agglomeration state [35]. Current studies confirm the toxicity of AgNPs to HepG2 and the impact are very contradictory depending on different NPs sizes, coating types and amounts considered: in general, the smaller AgNPs enter into HepG2 cells more efficiently and are more toxic than the larger ones.…”
Section: Discussionmentioning
confidence: 91%
“…Several reports show that AgNPs enter HepG2 cells localizing in the cytoplasm [34][35][36][37][38][39][40], nuclei [41] and mitochondria [35] at large amount irrespective of agglomeration state [35]. Current studies confirm the toxicity of AgNPs to HepG2 and the impact are very contradictory depending on different NPs sizes, coating types and amounts considered: in general, the smaller AgNPs enter into HepG2 cells more efficiently and are more toxic than the larger ones.…”
Section: Discussionmentioning
confidence: 91%
“…Both decreased [6,130] and increased [141] SOD activity has been observed. It was also found that exposure to AgNPs leads to a decrease in the activity levels of glutathione peroxidases in a human liver cell line [130].…”
Section: -Body Weight Gsh -Reduced Glutathione Ige -Immunoglobulin mentioning
confidence: 85%
“…This mechanism of AgNPs toxicity may be confirmed by the fact that weak antioxidants with -SH groups such as 2,3-dithiopropanol [26], N-acetylcysteine (NAC) [62], methionine and cysteine are more effective against AgNP-induced cytotoxicity than the most potent antioxidants without thiol groups such as Trolox (water soluble vitamin E analog) or Tempol [126]. Overproduction of ROS during exposure to AgNPs has been proven directly in several in vitro investigations [15,26,78,141] and also in vivo [30,103]. Among the oxidative stress-related changes caused by AgNPs, depletion of reduced glutathione (GSH) has been observed in human skin carcinoma cells [6], rat liver cells [60], mouse macrophage cells [100], human liver cells [106,141] and mouse embryonic fibroblasts [74].…”
Section: -Body Weight Gsh -Reduced Glutathione Ige -Immunoglobulin mentioning
confidence: 92%
See 1 more Smart Citation
“…_ 6 ) T D $ F I G ] coated AgNPs and silver ions were 84 and 25 mg/L in zebrafish (Bilberg et al, 2012). The 24-h IC 50 values of silver ions and citratecoated AgNPs were 0.5 and 50 mg/L for HepG2 cells (Vrček et al, 2014). In this study, the 24-h IC 50 values based on rat astrocyte cultures also showed that silver ions caused relatively higher cytotoxicity than AgNPs and the difference in the toxicities between these two silver species was approximate 10 folds.…”
Section: Discussionmentioning
confidence: 95%